2015
DOI: 10.1097/mao.0000000000000563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of a Polymerase Chain Reaction Assay in Culture-Negative Necrotizing Otitis Externa

Abstract: Patients who present with a refractory culture-negative NOE should be suspected as suffering from a fungal disease. The PCR assay may be an important laboratory adjunct in detecting pathogens responsible for NOE and can aid to promote therapy and disease resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Background Necrotizing (malignant) otitis externa is an aggressive, potentially life threatening infection occurring at the junction of the osseous and cartilaginous external auditory canal that can clinically resemble acute OE in its early stages [4]. Infection and inflammation spread from the osteocartilaginous junction or osseous canal along various anatomic routes; posteriorly toward the mastoid process, anteriorly/inferiorly via the fissures of Santorini ( Fig.…”
Section: Necrotizing Otitis Externa (Noe)mentioning
confidence: 99%
See 3 more Smart Citations
“…Background Necrotizing (malignant) otitis externa is an aggressive, potentially life threatening infection occurring at the junction of the osseous and cartilaginous external auditory canal that can clinically resemble acute OE in its early stages [4]. Infection and inflammation spread from the osteocartilaginous junction or osseous canal along various anatomic routes; posteriorly toward the mastoid process, anteriorly/inferiorly via the fissures of Santorini ( Fig.…”
Section: Necrotizing Otitis Externa (Noe)mentioning
confidence: 99%
“…The term NOE is used in the remainder of this discussion. NOE predominantly affects elderly patients, and patients with diabetes or other conditions resulting in immunodeficiency [4,[9][10][11]. It has been suggested that microangiopathy or altered immune function increases the risk of developing infection or perpetuates infection in the area [12,13].…”
Section: Necrotizing Otitis Externa (Noe)mentioning
confidence: 99%
See 2 more Smart Citations
“…42 Diagnosis is made by culture 41 or perhaps by polymerase chain reaction assay. 43 Uncomplicated cases may be treated with 2% acetic acid in propylene glycol or 1% clotrimazole solution. 41 Fungi are occasionally the etiologic agents in malignant otitis externa.…”
Section: Fungal Acute Otitis Externamentioning
confidence: 99%